Land use planning towards economic development and environment upgrading : a case study in Khao Kho, Petchabun, Thailand - Li, Lihua; Demaine, Harvey; Higuchi, Yoichiro\; Apisit Eiumnoh; Canadian International Development Agency (CIDA/ AIT - CUC/ PP 1988- 1993) (Bangkok : Asian Institute of Technology, 1991)
This research is aimed at achieving the sustainable development of the Khao Kho resettlement project in Pecthabun province of Thailand through the ecological feasible and socio economic viable land use planning and design. The physical land capability evaluation of the resettlement sites and the surrounding existing villages which were set up by previous RT A (Royal Thai A1my) land settlement scheme in 1980s and the assessment of the land use practice and socio-economic conditions in the RTA villages have been done in this study. Land use planning and recommendations are derived on the basis of land capability evaluation and the socio-economic assessment of the existing villages. For the assessment of socio-economic condition, SPSS statistical package was applied as the tool for statistical analysis. ARC/INFO - a GIS package and ERDAS - an image processing package were used as the tools for land evaluation and land use planning. The major conclusions drawn from the study are: most of the lands in the study area are not suitable for agriculture; settlers of RT A villages ure practicing inappropriate land use systems due to lack of labor and lack of knowledge/inf01mation of alternative sound land use system and financial resource. The agro-forestry system together with technical provision (agliculture extension service) should be promoted in the whole study area in both old RT A villages and new resettlement villages. And the scenarios for land allocation in the new villages and suggestions for project implementation toward the sustainable development are also provided.
A thesis submitted in partial fulfillment of the requirements for the award of the Degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Land use -- Thailand -- Phetchabun -- Planning